THE EFFECT OF PROGRESSIVE MUSCLE RELAXATION THERAPY IN DIABETES MELLITUS PATIENTS ON REDUCING BLOOD SUGAR LEVELS - Rahman, Irpan Ali (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
The increase in the number of Diabetes Mellitus sufferers will have an impact on physical and psychological conditions. The physical impacts are diabetic retinopathy, diabetic nephropathy, and diabetic neuropathy. Meanwhile, the psychological impact is the emergence of anxiety, anger, grief, shame, guilt, loss of hope, depression, loneliness, and hopelessness towards treatment. One non-pharmacological therapy to overcome the above phenomenon is the application of progressive muscle relaxation. Progressive muscle relaxation carried out continuously has a good impact on reducing blood glucose levels in Diabetes Mellitus patients. This study aims to identify a decrease in blood glucose levels in Diabetes Mellitus patients by implementing Progressive Muscle Relaxation. The research method used is a descriptive case study. The population and sample in this study was 1 Diabetes Mellitus patient. The results of the study showed that the patient experienced a decrease in blood glucose levels after Progressive Muscle Relaxation from 372 mg/dl to 240 mg/dl. This research concludes that there is an effect of Progressive Muscle Relaxation on reducing blood glucose levels in Diabetes Mellitus patients.